United Nations women's indicators and statistics database (WISTAT) - United Nations. Statistical Office (New York : United Nations, 1992)
Presents eighty-four spreadsheet tables containing data from 1970 to 1988 on women from 178 countries. Topics covered include education, housing, health, and crime.
Title from disk label.
Title on user's guide and reference manual: Wistat women's indicators and statistics spreadsheet database for microcomputers.
"Prepared by the Statistical Office Department of International Economic and Social Affairs United Nations Secretariat"--Label on container.
Issued also on 3 1/2 in. disks.
LC has 3 copies; 3rd copy missing user's guide and reference manual.
Keywords: Women -- Social conditions -- Statistics -- Databases; Women -- Economic conditions -- Statistics -- Databases